A-waves and electrophysiologically established diagnoses - (:unkn) unknown (My University, 2003)
The aim of this study was to investigate the presence of A-waves in cases referred to our electromyography laboratory with various diagnoses and documentation of electrophysiologic diagnoses with A-waves. In cases where at least 3 motor nerves were analysed, during F response studies, A-waves having stabile latencies and amplitudes from minimum one third of submaximal and supramaximal stimuli were evaluated. Electrophysiologic diagnoses and the related nerves of cases with A-waves were recorded. A-waves were obtained from 38 out of 1604 cases (2.36%). Most of the cases (57.8%) with established A-waves consisted of patients with radiculopathies. A-waves were detected mostly in tibial nerve. Electrophysiologic analysis of 5 cases with A-waves has given normal results. Although mechanism of A-waves is not known completely, we suggest when obtained it must be remarked during routine electrophysiologic examination.
Keywords: A-wave; Electrophysiologic diagnosis